ANALISIS PERAN PEMERINTAH TERHADAP PEMBANGUNAN INFRASTRUKTUR JALAN DAN PAJAK PENERANGAN JALAN BAGI KESEJAHTERAAN MASYARAKAT (Jurnal Ekonomi Bisnis dan Akuntansi, 2022)
The research in writing this journal aims to find out how the government's role in road infrastructure development, Road Lighting Taxes, obstacles in the implementation process and the solutions provided. This writing uses a qualitative analysis method with a descriptive approach or the so-called library approach related in the journal of road infrastructure and street lighting tax in East Java province. Telford road running. As for the role of the government in the street lighting tax, namely using taxes with diligence withholding. One of the problems is the budget process that has been disbursed for the design of its construction, but in fact there are still some that have not been disbursed and the participation of the people who still underestimate and have not paid according to the due date or exceeding the maturity date, the data may also not be included in the existing tax obligations in the government. With that, what is provided by the regional government is cooperation between development ratings, more optimization of infrastructure development plans, as well as increasing the quality and quantity of road infrastructure development projects so that they are more adequate with maximum results. In conclusion, the government's role in road construction and street lighting tax has actually been effective, but it has not been maximized in its implementation program.